Determination Analysis of Dish Collector Focal Shape in Vertical and Horizontal Direction of Concentrating Solar Power System - Dany Iman Santoso; Djatmiko Ichsani (Institut Teknologi Sepuluh Nopember, 2015)
A CSP (Concentrating Solar Power) system must have a receiver to receive solar ray reflection from parabolic dish collector. Based on the receiver installation to the collector, there are two type installation such as parallel to collector (horizontal direction) and perpendicular to collector (vertical direction). In this research not only we compared the receiver orientation but also we varied geometry concentration ratio. The experiment results show that the focal shape diameter elongates 2 mm and surface temperature increases 5-10°C for vertical orientation with greater concentration ratio. However, there is no significant effect to receiver with horizontal orientation. Thermal efficiency was affected by radiation and convection heat loss but for geometry concentration ratio above 100, radiation and convection heat loss gived small impact.